Impact of Disruptive Innovation in the Mobile Industry : Case Study Mobile Money Transfer in East Africa - Nyarega, Samuel Osoro (2014)
Research Background: In the current era of technological revolution, business firm is seeking for innovation in the technologies to enhance the business and ensure long term growth. Disruptive innovation in the mobile industry has brought a revolution of mobile money transfer, which has increased growth of mobile industry drastically. Purpose: The main purpose of this study is to evaluate the impact of disruptive innovation in the mobile industry through a case study of mobile money transfer in East Africa. Thus, for achievement of the purpose the main objectives developed by the researcher are to develop a conceptual understanding regarding the disruptive innovation and mobile money transfer, to critically evaluate the influence of disruptive innovation in the mobile industry, to explore the relationship between mobile money transfer and the development of the mobile industry in East Africa, to examine the impact of mobile money transfer in the development of the mobile industry. Methodology: In order to achieve the objectives of the study and fulfill its purpose, the researcher has implied a research methodology in this study, which included philosophy, approach, strategies and data collection methods. This research study is qualitative in nature and researcher has applied interpretivism philosophy and inductive approach along with the case study strategy, as this research issue is based on subjective nature. According to this, the data collection method used by the researcher is analysis of academic articles and reports, survey through questionnaire and focus group analysis. Findings: In order to analyze the data, a thematic framework analysis is used by the researcher. According to this analysis, the major findings of the study include, helps mobile industry in creating new markets and value network, assists mobile industry in its development and growth by bringing innovations, there is a relationship between mobile money transfer and development of the mobile industry and mobile money transfer facilitates mobile industry to attain growth in different developing countries. Recommendations: The proposed recommendations in this study are use of mobile money transfer facility, implementation of effective training program and develop a strong information and communication technology (ICT) system. Originality and further implications: This research study presents reliable and valid outcomes, which are based on originality, because the researcher has conducted both primary and secondary data analysis by using academic methods. The implications of this study are in the business world to understand the role of disruptive innovation in the mobile industry and for students to analyze that how disruptive innovation has been proven a major key determinant for the growth of mobile industry.